Common Precipitating Factors of Xerostomia in Elderly - Sutarjo, Femalia Nuril Ain; Rinthani, Maryam Fathiya; Brahmanikanya, Gisela Lalita; Parmadiati, Adiastuti Endah; Radhitia, Desiana; Mahdani, Fatma Yasmin (Journal of Health and Allied Sciences NU, 2023)
Xerostomia is a subjective sign of dry mouth t may or may not be accompanied by objective signs of hyposalivation. The condition of xerostomia has been associated with increasing age in line with the aging process, with a global prevalence of 30%. in the elderly aged 65 years and above. This can have an impact on the health and quality of life of the elderly. Also, xerostomia is the most common symptom in patients during periods of anxiety, stress, depression, radiotherapy, chemotherapy, and systemic diseases, as well as in individuals who have a history of polypharmacy or who use certain drugs. This study aimed to review the most recent available evidence regarding the most common causes of xerostomia in the elderly. The PCC strategy (population, context, and concept) was used as a guide for retrieving the relevant articles for this scoping review. Two databases were systematically searched using PubMed and Scopus. The draft of the scoping review and assessment of the methodological quality of the trials was carried out following the criteria of PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). A total of 12 trials were identified that met the previously defined selection and quality criteria; 9 related to medicine, and 4 included populations in which xerostomia was a systemic disease, rheumatic disease, radiation therapy to the head or neck region, nutrition, and psychological factors. The common precipitating factor of xerostomia in the elderly is medicine. Drugs that are more commonly found to cause xerostomia are gastrointestinal drugs, psychotropic drugs, and antihypertensive drugs.
Keywords: dry mouth; xerostomia; elderly; geriatric; human and health